2013
DOI: 10.1002/eji.201242902
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of dsRNA mimetics on cancer cells induces endogenous IFN‐β production capable of improving dendritic cell function

Abstract: Viral double-stranded RNA (dsRNA) mimetics have been explored in cancer immunotherapy to promote antitumoral immune response. Polyinosine-polycytidylic acid (poly I:C) and polyadenylic-polyuridylic acid (poly A:U) are synthetic analogs of viral dsRNA and strong inducers of type I interferon (IFN). We describe here a novel effect of dsRNA analogs on cancer cells: besides their potential to induce cancer cell apoptosis through an IFN-β autocrine loop, dsRNA-elicited IFN-β production improves dendritic cell (DC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…IFN-␤ is known to be a key molecule in antitumoral immune response in various cancers, including PCa (40,41). Moreover, in different cancer models, IFN-␤ has been shown to mediate poly(I:C)-dependent apoptosis or growth arrest (2,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␤ is known to be a key molecule in antitumoral immune response in various cancers, including PCa (40,41). Moreover, in different cancer models, IFN-␤ has been shown to mediate poly(I:C)-dependent apoptosis or growth arrest (2,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…This promotes the apoptosis of cancer cells via an autocrine signaling loop (35). Also, we have recently demonstrated that the levels of IFN-b produced by cancer cells stimulated with a TLR3 ligand are sufficient to improve the maturation state of DCs and reverse the suppressive effect of tumor cellderived factors on DC maturation (18)(19)(20). Thus, TLR3 agonists have been proposed to be multifunctional adjuvants promoting different antitumoral processes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when the therapeutic model was performed in TLR3-deficient mice, the inhibition of tumor growth lasted as long as the poly A:U treatment did (20). However, in physiological therapeutic settings in which poly A:U is administered to WT mice, The Journal of Immunologytumor growth control is much more robust and the effect lasts longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PolyIC is an attractive anti-tumor agent, as it can induce cancer cell apoptosis by activating Toll Like Receptor 3 (TLR3) in cancer cells [26]. Furthermore, TLR3 activation by polyIC triggers the induction of cytokines, chemokines and other pro-inflammatory mediators [710], thus reinstating anti-tumor immunity [11,12]. However, the use of polyIC is limited by its extreme toxicity and inefficient cellular uptake when delivered systemically [13,14].…”
Section: Introductionmentioning
confidence: 99%